Impact of the Levonorgestrel-Releasing Intrauterine System on the Progression of Chlamydia trachomatis Infection to Pelvic Inflammatory Disease in a Baboon Model. (15th December 2017) - Eastman, Alison J; Bergin, Ingrid L; Chai, Daniel; Bassis, Christine M; LeBar, William; Oluoch, George O; Liechty, Emma R; Nyachieo, Atunga; Young, Vincent B; Aronoff, David M; Patton, Dorothy L; Bell, Jason D
Abstract : In baboons with the levonorgestrel-releasing intrauterine system and Chlamydia trachomatis infection, progression to pelvic inflammatory disease may not be affected, but infection lasts longer and yields higher titers relative to infected controls. Defects in early activation of the interleukin 1 pathway may account for this difference. Abstract: Background: Understanding the relationship between the levonorgestrel (LNG)–releasing intrauterine system (IUS) and sexually transmitted infections (STIs) is increasingly important as use of the LNG-IUS grows to include women at higher risk for STIs. This study assessed the impact of the LNG-IUS on development of Chlamydia trachomatis pelvic inflammatory disease, using a baboon model. Methods: Baboons with and those without the LNG-IUS were cervically inoculated with C. trachomatis and monitored daily, and cervical and fallopian tube swab specimens were collected weekly for C. trachomatis quantitation by nucleic acid amplification testing and culture. Vaginal swab specimens were collected for cytokine analysis, and serum samples were obtained for detection of C. trachomatis antibodies. Results: The LNG-IUS resulted in an increased C. trachomatis burden in the cervix, with the bacterial burden in the LNG-IUS group diverging from that in the non–LNG-IUS group by 6 weeks after infection. One of 7 baboons in the non–LNG-IUS group and 2 of 6 in the LNG-IUS group developed pelvic inflammatory disease, while 3 animals in each group met criteria suggestive of pelvic inflammatory disease. LNG-IUS increased baseline interleukin 8 levels but failed to further upregulate interleukin 8 during infection. In LNG-IUS recipients, early perturbations in the interleukin 1β axis corresponded to decreased C. trachomatis clearance and increased T-helper type 2 immune responses. Conclusion: LNG-IUS use results in delayed clearance of C. trachomatis and might alter the reproductive tract immune environment.